Beyond Collective Agreements: The Rise of the Wage Cushion in Germany - André Rieder; Claus Schnabel (Institute of Labor Economics (IZA), 2025)
Representative establishment data reveal that over 60 percent of German plants covered by collective agreements pay wages above the level stipulated in the agreements, creating a wage cushion between actual and contractual wages. While collective bargaining coverage has fallen over time, the prevalence of wage cushions has increased, particularly in eastern Germany. Cross-sectional and fixed-effects analyses for 2008-2023 indicate that in western Germany the presence of a wage cushion is mainly related to plant profitability, unemployment, vacancies, and the business cycle. Plants which apply collective agreements at the firm rather than the sectoral level are less likely to have wage cushions since firm-level agreements make it easier to explicitly take firm-specific conditions into account. In eastern Germany, however, the explanatory power of these variables is considerably lower. Against the backdrop of falling bargaining coverage, the increasing prevalence of wage cushions suggests that the traditionally rigid German system of wage determination has become more flexible and differentiated.
Keywords: J30; J31; 330; wage determination; collective bargaining; wage cushion; Germany